A Study on Milling Parameters for Enhanced Surface Quality of FDM-Printed PLA Parts - Dr. Felho, Csaba; Mehdiyev, Ziya (International Journal of Integrated Engineering, 2024)
Fused Deposition Modeling (FDM) is a mostly used additive manufacturing method known for its cost-effectiveness and ease of use in producing parts with complex geometries. However, there are also several challenges such as surface roughness which limit its applications where surface quality is a critical factor. Post-processing methods - including milling, have been analyzed to improve the surface quality of FDM-printed parts. This paper focused on optimizing milling parameters for PLA thermoplastic parts manufactured via FDM. A series of systematic experiments changing spindle speed, feed rate, and tool radius were investigated to determine the ideal combination for getting optimal milling results. The gathered results showed that a spindle speed of 1500 RPM and a feed rate of 500 mm/min with a 4 mm radius milling tool represented the best surface quality and dimensional accuracy. Practical applications include streamlined manufacturing processes and improved part quality, improving the usability of FDM-based manufacturing. Further research works are recommended to investigate advanced processing techniques and parameter optimization methods to unlock the full potential of this technology.